Achievements and shortcomings of the Ceibal digital education system in Uruguay and its implication for Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2023)
The suspension of lessons due to health regulations, during the Covid-19 pandemic, exposed the relevance, for teachers and students, of computers and internet connection. Costa Rica suffered for its failure to foresee these requirements. This essay exposes Uruguay's Ceibal Plan, whose educational resilience represented a positive contrast worldwide. Its experience was a systemic political-educational paradigm. Since 2007, computers were distributed and Internet connectivity was ensured for teachers and students, and teacher training was provided with online didactic resources. Studies point to shortcomings that are also noted. Their reduced social appropriation produced decreased teacher's interest in using these resources. Its educational digital heritage is highlighted and the necessary conditions for its replication are emphasized.
Keywords: Ceibal Plan; Uruguay; digital education; internet; constructivism; constructionism